2013
DOI: 10.1523/jneurosci.2205-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Coding the Meaning of Sounds: Contextual Modulation of Auditory Responses in the Basolateral Amygdala

Abstract: Female mice emit a low-frequency harmonic (LFH) call in association with distinct behavioral contexts: mating and physical threat or pain. Here we report the results of acoustic, behavioral, and neurophysiological studies of the contextual analysis of these calls in CBA/CaJ mice. We first show that the acoustical features of the LFH call do not differ between contexts. We then show that male mice avoid the LFH call in the presence of a predator cue (cat fur) but are more attracted to the same exemplar of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 45 publications
2
66
1
Order By: Relevance
“…Romanski and Averbeck suggested that one way to demonstrate semantic categorization in the brain would be to show that sounds with similar acoustic morphology but different semantic context evoke different neural responses (Romanski & Averbeck, 2009). Interestingly, the activity of neurons in the male mouse basolateral amygdala in response to the same female vocalization is modulated by the context (predator cue vs. mating cue), whereas it is not when the sound presented in these two contexts is a burst of noise (Grimsley et al, 2013). This differential neuronal activity is correlated with male mouse behavior in response to the same vocalization (escape in the presence of the predator cue, and approach in the presence of the mating cue).…”
Section: Disentangling Semantic Categorization From Acoustic Categorimentioning
confidence: 99%
“…Romanski and Averbeck suggested that one way to demonstrate semantic categorization in the brain would be to show that sounds with similar acoustic morphology but different semantic context evoke different neural responses (Romanski & Averbeck, 2009). Interestingly, the activity of neurons in the male mouse basolateral amygdala in response to the same female vocalization is modulated by the context (predator cue vs. mating cue), whereas it is not when the sound presented in these two contexts is a burst of noise (Grimsley et al, 2013). This differential neuronal activity is correlated with male mouse behavior in response to the same vocalization (escape in the presence of the predator cue, and approach in the presence of the mating cue).…”
Section: Disentangling Semantic Categorization From Acoustic Categorimentioning
confidence: 99%
“…Studies on mice have shown that neurons in the basolateral amygdala exhibit early excitation to sociallyrelevant auditory stimuli (conspecific calls), and that this response is modulated by the non-auditory context (e.g. threatening or mating cues) (Grimsley et al, 2013). Importantly, the non-auditory context does not modulate the amygdalar response to non-socially-relevant sounds (e.g.…”
Section: Amygdalamentioning
confidence: 99%
“…The ratio of stimulus-selective cells to all recorded cells was larger in the surrounding arcopallium (34.1%) than in the TnA (20.3%), suggesting that neurons in this area can represent behavioral relevance of stimuli and be involved in recognizing vocalizations and controlling successive behaviors. Recently, neural activity in the amygdala, especially in the lateral or basolateral subdivision, has been investigated in rodents and bats [Naumann and Kanwal, 2011;Gadziola et al, 2012Gadziola et al, , 2016Parsana et al, 2012;Peterson and Wenstrup, 2012;Grimsley et al, 2013]. In the rat lateral amygdala, it has been known that neurons respond to the cue tones in the fear conditioning [LeDoux et al, 1990].…”
Section: Evolutional Perspectivementioning
confidence: 99%
“…The authors reported that 82% of recorded cells were auditory responsive, which is comparable to our results in the TnA (68.7%) and in the surrounding arcopallium (72.4%). Grimsley et al [2013] demonstrated that neurons in the mouse basolateral amygdala are activated when listening to behaviorally aversive vocalizations and that the activity is modulated by visual cues associated with predation. In bats, the neurons in the lateral [Gadziola et al, 2012] or basolateral amygdala [Naumann and Kanwal, 2011;Peterson and Wenstrup, 2012;Gadziola et al, 2016] respond selectively to specific social calls.…”
Section: Evolutional Perspectivementioning
confidence: 99%